Ecological drivers of pteridophyte diversity and distribution in Togo (West Africa) - Abotsi, K.E.; Bose, R.; Adjossou, K.; Deblauwe, V.; Rouhan, G.; Segla, K.N.; Atsri, K.H.; Kokou, K. (Elsevier, 2020)
The conservation and sustainable management of biodiversity requires an understanding of the biotic and abiotic factors that condition the presence and survival of organisms in natural habitats. The global distribution and ecological hypersensitivity of pteridophytes have made them ideal candidates for studying the impact of biotic and abiotic factors on levels of biodiversity.